PROGRAM STUDI AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS 17 AGUSTUS 1945 SAMARINDA - Putri, Riska Diana (EKONOMIA, 2019)
The researchers really wanted to know the causes of errors and mistakes that often occur, including missing inventory items, as well as the purpose of this study, so that researchers know the internal control procedures contained in the trading company, so that the company gets additional insight into control procedures internally in accordance with the existing Internal Control Standards, as well as adding insight and references to the reader. The basic theory in this research is Accounting Information System, Accounting Information System is an information system that handles everything related to Accounting. The inventory accounting system aims to record the mutations of each type of inventory stored in the warehouse. Inventory security issues are the main problem experienced by every type of trading business. A good inventory internal control procedure is needed by trading companies because this is able to minimize these risks. based on the description, this study takes the title